Teaching English using Delegator Teaching Style for Aviation Cadets: An Autoethnography - Raga Pratama; Siusana Kweldju (Universitas Nusantara PGRI Kediri, 2026)
This autoethnography explores my five-year journey of employing a delegator teaching style to instruct English for Specific Purposes (ESP) to aviation cadets in an Indonesian aviation academy. It delves into the practical application of this student-centered approach within a highly specialized and often hierarchical training environment. Through personal narratives, reflections, and an analysis of classroom dynamics, this study examines the successes, challenges, and evolution of my pedagogical practice. Furthermore, it critically investigates the connection between the delegator teaching style and the facilitation of deeper learning, characterized by critical thinking, problem-solving, collaboration, and self-directed learning, essential for the future careers of aviation professionals. The Indonesian socio-cultural context, the unique demands of aviation English, and the inherent characteristics of the cadets are interwoven throughout the narrative to provide a rich, contextualized understanding of this pedagogical experience. This work aims to offer insights for educators in similar specialized vocational settings, particularly within the Indonesian or Southeast Asian context.